Perancangan Progressive Dies Pelat untuk Draft Mark Kapal - M. Jundy Auzan Fanony; Pranowo Sidi; Budianto Budianto (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
One of the production processes in the manufacturing industry is Progressive Dies, in thisprocess the manufacture of products consists of many processes that are interconnected with a singlepress can produce various cutting results derived from the same material (coil). This study made animage design of Progressive Dies plates for the Draft Mark of ships with the help of Catia softwareand the making of simulations so that they could find out the description of the cutting process. Beforedesigning the Progressive Dies engine, calculations are needed - calculations needed such as,clearance, cutting force, stripper force, die thickness, engine tonnage, and deflection that occurs onthe die. From the calculation of the force required to punch a plate with a thickness of 2mm is 72 tons.From the calculation results continued with the analysis using Element Method Until with the help ofcatia software obtained the highest stress result is 1.81 x 108 N / m2 with the result is smaller thanthe dies material tensile stress used (SKD11). And the maximum deflection value that occurs is belowthe maximum deflection value that is permitted, so the results meet the conditions accepted.